Surgical tactics of treatment of the wounded persons with the gun-shot injuries of the hip on all levels of medical support - I. P. Khomenko; S. О. Коrol; B. V. Matviichuk; L. А. Ustinova (Клінічна хірургія)
Objective. To substantiate the introduction of differentiated surgical tactics, taking into account the trauma severity for improvement of the treatment results in the wounded persons, suffering the gun-shot injuries of the hip (GSIH).